2021
DOI: 10.1371/journal.pone.0245522
|View full text |Cite
|
Sign up to set email alerts
|

Altitude and the distributional typology of language structure: Ejectives and beyond

Abstract: The first decades of the 21st century have witnessed a renewed interest in the relationship between language structure and the various social and ecological niches in which the languages of the world are used and against the background of which they evolved. In this context, Everett (2013) argued for direct geographical influences on the sound structure of languages. It was observed that ejective consonants, produced with a sudden burst of non-pulmonic air to a salient acoustic effect, tend to occur in high-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…As in the case of the click-related hypothesis, however, this suggestion remains speculative. Recent work replicates the key finding in Everett [39] with a much larger sample of languages, finding a significant worldwide correlation between ejectives and altitudes [40]. However, that work also questions the interpretation of the distribution offered in Everett [39], while acknowledging that room for such an interpretation remains [40].…”
Section: Consonantsmentioning
confidence: 58%
“…As in the case of the click-related hypothesis, however, this suggestion remains speculative. Recent work replicates the key finding in Everett [39] with a much larger sample of languages, finding a significant worldwide correlation between ejectives and altitudes [40]. However, that work also questions the interpretation of the distribution offered in Everett [39], while acknowledging that room for such an interpretation remains [40].…”
Section: Consonantsmentioning
confidence: 58%
“…This high-altitude distribution was also recently supported with a much larger dataset, though the study in question also found support for a weaker association between uvular phonemes and high elevation. (Urban & Moran 2021) The latter association hints that the ejective-altitude correlation is likely spurious. In other work I test the frequency of ejective consonants in phonetically transcribed word lists from 1,991 dialects, once again using the ASJP database, along with numerous other consonant types.…”
Section: Potential Adaptations Owing To Environmental Variation Acrosmentioning
confidence: 99%
“…Associations of this type can be used as starting points to further inquiry, though in the case of ejectives there are reasons to doubt that the association is due to the motivation suggested in Everett (2013). (Urban & Moran 2021) Figure 2. Locations of 176 dialects whose Swadesh-type word lists contain ejective consonants, out of 1,991 tested in Everett (in progress).…”
Section: Potential Adaptations Owing To Environmental Variation Acrosmentioning
confidence: 99%
See 2 more Smart Citations